Haematological studies in apparently normal five indigenous breeds of goats in Nigeria - Aba-Adulugba, E.; Joshua, R.A. (1990)
Eleven haematological parameters were studied in apparently normal 210 goats comprising five breeds from Nigeria. Haematological values were compared and contrasted for the five breeds. The mean RBC counts were least (7.09 x 106/cc) for the West African Dwarf (WAD) goats and highest (8.79 x 106/cc) for the Kano brown. The mean PCV values were highest for Salla (29.31 %) and lowest for WAD 23.6%). The haemoglobin concentrations for four breeds were very similar (9.21-9.99mg/dl) but the WAD had a value of 7.73mg/dl. The mean values for three erythrocytic indices (MCV, MCH and MCHC) in the 5 breeds were similar. The MCHC, PVC and RBC values in all breeds studied tend to decrease in goats aged five years and above. The decrease was not found very significant (P>0.05). Breed significantly affects none of the eleven parameters. Total eucocytes and differential leucocyte counts were generally not affected by breed or age. The Bororo white, Salla and Kano brown had apparently high neutrophil counts. The highest mean for lymphocytes was observed in the WAD while the Borono white goats had the lowest count.